Evaluation of naturally occurring radioactive materials (NORM) in the soil, in a potential area for unconventional reservoirs in the Rancheria Sub-Basin. (November 2021) - Salazar, S.; Castillo, L.A.; Montes, L.
Abstract: Naturally occurring radioactive elements depend on lithology geogenic characteristics, such as depositional, environmental, or diagenetic. Thus, evaluating these elements constitutes a tool to define ionizing radiation effect from rocky sequences. This study carried out in the Rancheria Sub-Basin establishes both characterization and assessment of this kind of material, known as NORM. The sampling included uranium-238, thorium-232, potassium-40, radon-226, and radon-222 in soil samples, cutting samples from the Molino-1 well, and radon in surface water. Bases on a radiometric methodology with a gamma-ray spectrometer for uranium-238, thorium-232, and potassium-40 and emanometric with ionizing chambers for radio-226 and radon-222. The analysis and results of the activity concentrations in soil samples of U-238, Th-232, K-40, and Ra-226 are 11.7 BqKg −1, 33.0 BqKg −1, 424.5 BqKg −1, and 15.59 BqKg - 1, respectively, among the acceptable global averages. However, in some areas, observed values indicate high activity concentrations of U-238, Th-232, K-40, Ra-226, and Rn-222 in the soil of 50.2 BqKg −1, 62.8 BqKg −1, 1596.3 BqKg −1, 44.25 BqKg −1, and 112546.79 Bqm −3, respectively. Those activity concentrations were associated with zone lithology. Highlights: Study the activity concentration of uranium-238, thorium-232, potassium-40, radon-226, and radon-222 gas on the surface. Distribution of the potential Geogenic Radon verifies in unconventional deposits. Background of uranium, thorium, potassium, and radium permit characterize their emission on the surface. Ionizing Radiation could associate with hydrocarbon presence. Ionizing radiation occurs naturally in fine-grained rocks with high content organic matter.